Réponses

2013-12-04T23:58:19+01:00
A=3(x-3)+8(x-3)=(x-3)(3+8)=11(x-3)

B=5(x-3)^2-x(x-3)=(x-3)(5(x-3)-x)=(x-3)(5x-15-x)=(x-3)(4x-15)

C=(x+2)(x-3)+3x(x-3)=(x-3)(x+2+3x)=(x-3)(4x+2)=2(x-3)(2x+1)

D=(x-3)^2-2x(x-3)=(x-3)(x-3-2x)=(x-3)(-x-3)

E=x(4x-6)-2(x-3) ---> pas de facteur commun

F=(x-3)^2-(x-3)=(x-3)(x-3-1)=(x-3)(x-4)
2013-12-05T00:00:08+01:00
A = 3(x-3)+8(x-3)
A = (x-3)(3+8)
A = 11(x-3)

B = 5(x-3)²-x(x-3)
B = (x-3)(5(x-3)-x)
B = (x-3)(4x-15)

C = (x+2)(x-3)+3x(x-3)
C = (x-3)((x+2)+3x)
C = (x-3)(4x+2)

D = (x-3)²-2x(x-3)
D = (x-3)((x-3)-2x)
D = (x-3)(-x-3)

E = x(4x-6)-2(x-3)
E = 2x(2x-3)-2(x-3)
E = 2(x(2x-3)-(x-3))

F = (x-3)²-(x-3)
F = (x-3)((x-3)-1)
F = (x-3)(x-4)